Intelligent Automation in SAP Credit Release: Eliminating Manual Bottlenecks in Sales Order Processing - Reddy Tatavandla, Vishnuvardhan (International Journal of Computational and Experimental Science and Engineering, 2025)
Effective credit management in high-volume manufacturing and distribution environments, such as the SAP ERP Central Component (ECC), is crucial for maintaining an enterprise’s financial stability. Despite its critical role in risk management, the sales Order credit block mechanism inherently causes substantial operational delays. This study investigates how the manual resolution of credit blocks in traditional SAP ECC leads to unpredictable bottlenecks in the order-to-cash cycle, adversely affecting delivery delays, working capital, delaying cash collection, and diminishing the customer experience. By substituting inefficient manual processes with a rapid, consistent, and transparent automated system, organizations can significantly mitigate, thereby directly expediting the cash conversion cycle. This study demonstrates that the architectural shift from manual ECC workflows to intelligent automation in S/4HANA and BTP represents a fundamental paradigm shift, enabling proactive risk management rather than reactive bottleneck resolution.